Hypertensive Disease: History of Nosology Development (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents data from domestic and foreign literature on the evolution of ideas about hypertension and the evolution of manifestations of the disease or its clinic. The concept of the mechanisms of development of arterial hypertension is presented in detail.